2011
DOI: 10.4028/www.scientific.net/amr.287-290.2028
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Property of Biomaterial Carotenoids Production by Rhodobacter Sphaeroides WL-APD911

Abstract: A Rhodobacter sphaeroides WL-APD911 with the capability of producing the end products of neurosporene and ξ-carotene, rather than the normal end products of spheroidene, was isolated from hundreds of strains by using chemical mutagenesis. The strain WL-APD911 grew well in LB medium, and the colored carotenoids were produced within 3 days of incubation at 30°C. The Rs-M of colored carotenoid extracts obtained from strain WL-APD911 by using methanol extraction inhibited the NO production and iNOS expression by L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Meanwhile, neurosporene itself has the ability to protect irradiation with UV-B [10]. Lycogen™ inhibited NO production and iNOS expression in activated macrophages [3] and was capable of improving colonic damage in DSS-induced colitis [4]. Further work is warranted to elucidate the active ingredient(s) in Lycogen™ for hypopigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, neurosporene itself has the ability to protect irradiation with UV-B [10]. Lycogen™ inhibited NO production and iNOS expression in activated macrophages [3] and was capable of improving colonic damage in DSS-induced colitis [4]. Further work is warranted to elucidate the active ingredient(s) in Lycogen™ for hypopigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Some probiotics have immunomodulatory activities and modulate the symptoms of several diseases. Previously, we found that the extracts of Rhodobacter sphaeroides (Lycogen™) inhibited nitric oxide production and inducible nitric-oxide synthase expression in activated macrophages [3]. Meanwhile, the effect of Lycogen™, a potent anti-inflammatory agent, was evaluated in mice with dextran sodium sulfate (DSS)-induced colitis.…”
Section: Introductionmentioning
confidence: 99%
“…A mutant strain capable of producing colored carotenoids, in contrast to the colorless phenotype of the wild type, was isolated from among hundreds of strains using a chemical mutagen sodium azide (NaN 3 ) ( 18 ) ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lycogen™ has attracted significant attention because of its promising biotechnological potential as demonstrated in our previous studies ( 18 – 20 ). For example, Wu and Liu reported that R. sphaeroides (WL-APD911) grew well in LB medium, and the extract Lycogen™ had the ability to inhibit NO production and iNOS expression in LPS-induced RAW 264.7 cells.…”
mentioning
confidence: 94%
See 1 more Smart Citation